A multi-arm phase Ib/II study designed for rapid, parallel evaluation of novel immunotherapy combinations in relapsed/refractory acute myeloid leukemia. Issue 9 (29th July 2022) - Short, Nicholas J.; Borthakur, Gautam; Pemmaraju, Naveen; Dinardo, Courtney D.; Kadia, Tapan M.; Jabbour, Elias; Konopleva, Marina; Macaron, Walid; Ning, Jing; Ma, Junsheng; Pierce, Sherry; Alvarado, Yesid; et al.
Abstract: We conducted a phase Ib/II multi-arm, parallel cohort study to simultaneously evaluate various immunotherapeutic agents and combinations in relapsed/refractory acute myeloid leukemia (AML). Overall, 50 patients were enrolled into one of 6 arms: (A) single agent PF-04518600 (OX40 agonist monoclonal antibody), (B) azacitidine + venetoclax + gemtuzumab ozogamicin (GO), (C) azacitidine + avelumab (anti-PD-L1 monoclonal antibody) + GO, (D) azacitidine + venetoclax + avelumab, (E) azacitidine + avelumab + PF-04518600, and (F) glasdegib + GO. Among all regimens evaluated, azacitidine + venetoclax + GO appeared most promising. In this arm, the CR/CRi rates among venetoclax-naïve and prior venetoclax-exposed patients were 50% and 22%, respectively, and the 1-year OS rate was 31%. This study shows the feasibility of a conducting a multi-arm trial to efficiently and simultaneously evaluate novel therapies in AML, a needed strategy in light of the plethora of emerging therapies. This trial was registered at www.clinicaltrials.gov as NCT03390296.